The Expressions of Political Power in Panoramic and Grand Space in Ancient Roman Empire before A.D. 476 (British Journal of Multidisciplinary and Advanced Studies, 2023)
This article argues the occupation, penetration and radiation of political power in the panoramic space by explaining the typical public architecture and public space in the former Roman Empire. As the most important public space, squares are the places where emperors show their powers. So the political elites try to occupy it. In Colosseum the emperors’ supreme power is thoroughly and incisively expressed by the carefully designed space settings. The public baths with compound decorations and functions are the visual panoramic scene. In this entertaining public space political power penetrates the individual life. The grandness of public architectures in roman city are the result of powers’ ostentation. With the imperial structure the styles and functions of public architectures in roman city radiates the whole empire. With these three relations between power and space this article draws two conclusions. First the ostentatious power based on the competitive power system is the connector between the republic and early empire. The great achievements in public architecture are the fruits of it. Second the super grand territory is the result of the links between military and politics. This links lead to the competitive power system. It also explains why the roman empire is invaded by the barbarians in the west but it continues in the east.